2017
DOI: 10.1186/s12014-017-9165-x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular abundance of complement proteins characterized by proteomic analysis of laser-captured microdissected glomeruli associates with progressive disease in IgA nephropathy

Abstract: BackgroundThe clinical course of IgA nephropathy (IgAN) is variable and complement activation may predict prognosis. The present study investigated whether glomerular abundance of complement proteins associates with progression to end-stage renal disease (ESRD) in patients for whom prognosis could not be predicted based on clinical variables.MethodsBased on data from the Norwegian Kidney Biopsy Registry and the Norwegian Renal Registry, three groups were included: IgAN patients with (n = 9) or without (n = 16)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 27 publications
3
55
0
Order By: Relevance
“…In our study, we found that microangiopathy was associated with C4d, C1q, and C5b-9 deposits; in contrast, MBL deposits were not detected in most patients, even after we repeated the experiment using different anti-MBL antibodies or using fresh-frozen tissue samples (data not shown). Proteomics-based analyses of laser-captured microdissected glomeruli revealed that the classical pathway components C1q, C1r, and C1s were significantly higher in patients with progressive IgA nephropathy compared to patients with non-progressive IgA nephropathy [48]. These data suggest that C4d may reflect activation of both the lectin and classical pathways in IgA nephropathy.…”
Section: Discussionmentioning
confidence: 81%
“…In our study, we found that microangiopathy was associated with C4d, C1q, and C5b-9 deposits; in contrast, MBL deposits were not detected in most patients, even after we repeated the experiment using different anti-MBL antibodies or using fresh-frozen tissue samples (data not shown). Proteomics-based analyses of laser-captured microdissected glomeruli revealed that the classical pathway components C1q, C1r, and C1s were significantly higher in patients with progressive IgA nephropathy compared to patients with non-progressive IgA nephropathy [48]. These data suggest that C4d may reflect activation of both the lectin and classical pathways in IgA nephropathy.…”
Section: Discussionmentioning
confidence: 81%
“… 53 In a proteomic analysis, glomerular FHR5 was 1.79 times more abundant in patients with progressive versus stable IgAN. 54 FHR5 antagonizes the ability of fH to negatively regulate C3 activation. 55 , 56 Consequently, it was interesting that patients with progressive disease had more cases of glomerular FHR5 staining in the absence of fH.…”
Section: Discussionmentioning
confidence: 99%
“…Application of this novel technique to the diagnosis of glomerulonephritis has just begun. To date, IgA nephropathy (IgAN) has been analysed in a few studies, with a focus mainly on deposited immunoglobulin and complements . In our study, we analysed the glomerular proteomics of IgAN and membranous nephropathy (MN) by LMD and LC‐MS/MS and we compared our findings with those for normal glomeruli obtained at biopsies from kidney transplant donors.…”
Section: Introductionmentioning
confidence: 99%
“…To date, IgA nephropathy (IgAN) has been analysed in a few studies, with a focus mainly on deposited immunoglobulin and complements. 6,7 In our study, we analysed the glomerular proteomics of IgAN and membranous nephropathy (MN) by LMD and LC-MS/MS and we compared our findings with those for normal glomeruli obtained at biopsies from kidney transplant donors. Moreover, we investigated the significance of the detected molecules with regard to the diagnosis and pathogenesis of glomerular diseases.…”
mentioning
confidence: 99%